Percutaneous Biliary External–Internal Drainage for Malignant Obstruction of Self-Expanding Uncovered Metal Stents Placed for Hilar Carcinoma: Retrospective Analysis of Long-Term Outcome in 160 Patients - Bonnel, Didier H.; Gangloff, Alice; Fingerhut, Abe (Journal of Clinical Interventional Radiology ISVIR, 2020)
Aims and Objectives We evaluated the safety and effectiveness of reestablishing adequate bile flow in patients with malignant obstruction of multilobar self-expanding uncovered metal stents (SEUMSs) inserted for palliative treatment of malignant hilar stenosis, an otherwise fatal setting. From September 1991 to January 2019, 160 patients (100 men and 60 women; median: 69 [range: 37–87] years) with malignant obstruction of multilobar SEUMSs were treated by percutaneous transhepatic external–internal biliary drainage. All patients were followed in their respective oncology services where they were treated (or not) according to local protocols adapted to their disease and overall general status.Result External–internal biliary drainage was successful in all 160 patients. All patients were discharged within 5 days. Both immediate (4 patients; 2.5%) and late complications (29 patients; 18%) were managed successfully with minimal morbidity and no mortality. After reestablishment of adequate bile flow, the median survival was 191 days (range: 2–5,668 days). Forty-one (25.6%) patients survived for more than 12 months, and 10 (6.2%) survived for more than 3 years.Conclusion In our series, external–internal biliary drainage was safe and effective; it was life-saving and afforded acceptable quality of survival for patients who otherwise would have been left untreated with short-term fatality.
Keywords: percutaneous biliary stent; bile duct malignancy; hilar carcinoma; biliary stent obstruction